1994
DOI: 10.1109/23.340613
|View full text |Cite
|
Sign up to set email alerts
|

Hardness variability in commercial technologies

Abstract: budgets, there has been a drastic decrease in the dollar value of the radiation-hardened integrated circuit The radiation hardness of commercial Floating (IC) market, and a concomitant reduction in the Gate 256K E2PROMs from a single diffusion lot number of viable suppliers of radiation-hardened was observed to vary between 5 to 25 krad(Si) when ICs. This trend is expected to continue for the foreirradiated at a low dose rate of 64 mrad(Si)/s. Addi-seeable future. In addition, the capability of radiational var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Previously, tests on commercial parts from different manufacturers had shown large variations in hardness, even across wafers [13,17,18]. What was pointed out in a study led by the CERN Microelectronics Group [19] was that 0.25 mm CMOS transistors showed especially good behaviour compared to coarser technologies in leakage current, threshold voltage shifts and transconductance behaviour at Mrad levels and the results suggested that higher doses could be tolerated.…”
Section: Deep Sub-micron Cmos Technologymentioning
confidence: 96%
“…Previously, tests on commercial parts from different manufacturers had shown large variations in hardness, even across wafers [13,17,18]. What was pointed out in a study led by the CERN Microelectronics Group [19] was that 0.25 mm CMOS transistors showed especially good behaviour compared to coarser technologies in leakage current, threshold voltage shifts and transconductance behaviour at Mrad levels and the results suggested that higher doses could be tolerated.…”
Section: Deep Sub-micron Cmos Technologymentioning
confidence: 96%
“…Most standard commercial devices fail somewhere in the range of 3-30 krad (SiO 2 ) [6]. However, higher dose rad-hard electronics can be fabricated depending upon the specific needs at higher cost due to their very limited market.…”
Section: Effects Of Radiation On Devicesmentioning
confidence: 99%
“…Total-dose hardness requirements in krad (Si) for several satellite systems as a function of orbit altitude (After Ref 6). …”
mentioning
confidence: 99%
“…Most standard commercial devices fail somewhere in the range of 3-30 krad(SiO2) [5], [43], [44]. However, there are recent reports of parts fabricated in at least one commercial foundry with hardness greater than 100 krad(SiO2) [45], so one must take care not to over-generalize conclusions in this area.…”
Section: Device Radiation Responsementioning
confidence: 99%
“…2 shows total dose levels for some systems with which Sandia National Laboratories has been involved in the past [43]. Clearly, low-Earth orbits are generally more benign than higher orbits.…”
Section: Device Radiation Responsementioning
confidence: 99%